(3eTjNI GHf GdfMGSs - (3YHO GdQMef Hf YeQ Hf eMeO Hf SYjO, CHh eMeO GdJLjHj GdeYQha H` GHf GdfMGS,J (B416 (3g` s
(3ChdgG (B:s
(3CNHQfG GdTjN GdUGdM CHhYHOGddg GdMSjf Hf CHj GdaNQ GdHUQj s
(3HgG SeGY Ydi CHj YHOGddg GdMSjf Hf CHj GdaNQ GdHUQjs
(3hHBNQgG SeGYGJ cKjQI efgG hSeGY HNW GdMGaX YHOGdYXje GdoefPQi SfI (B637 (3g`s
(3PcQ ajg TjhNg GdPjf SeY efge hQhi Yfges
(3bQf GdfSN (B:s
(3GdbQf GdSGHYs
(3GdJhKjbGJ GdeQLYjI (B:s
Keywords: (3GdJGQjNs